Ultrasound guidance during hysteroscopic myomectomy in G1 and G2 Submucous Myomas: for a safer one step surgery. (August 2016) - Korkmazer, Engin; Tekin, Başar; Solak, Neşe
Abstract: Objective: Hysteroscopic myomectomy is the gold standard method for treatment of submucous fibroids. Hysteroscopic myomectomy techniques for removal of submucous fibroids still have controversies. In this study we aimed to describe usefulness of ultrasound guidance in hysteroscopic myomectomy for a safe and effective removal of submucous G1 and G2 fibroids. Study design: This is a multicentre study. 64 symptomatic patients with submucous fibroid underwent ultrasound guided hysteroscopic myomectomy. First we excised intrauterine dome of fibroid until reaching the level of cavity wall by the method of resectoscopic (electrosurgical resection using a loop electrode) slicing. Next remnant intramural node was squeezed by uterine contractions induced. After we had excised the intrauterine dome of fibroid by slicing method, we formed cavitation for the intramural part (newly raised myoma dome). The cavity was filled with distension solution and we evaluated the margins of the uterus and the margins of the myoma by sonographically. Then the myoma was excised under ultrasonographic guidance by transabdominal probe. We obtained a regular uterine cavity. Results: Mean operation time was 42 ± 7 min. Mean Mannitol volume was 4.3 ± 1.7 l and the mean intraoperational fluid deficit was 500 ml. Not in any case uterine perforation was occurred. All fibroids removed totally. In 8 (19%) cases intrauterine synechiae detected and all these synechiaes were incised by a scissor during hysteroscopy. Conclusion: There is still no single technique proven to be unequivocally superior to the others for treating fibroids with intramural development (G1–G2). Ultrasound guided hysteroscopy seems to be an effective and safe method for resection of G1 and G2 fibroids.